Efficient One-Step Immobilization of CaLB Lipase over MOF Support NH2-MIL-53(Al) - Victoria Gascón-Pérez; Mayra Belen Jiménez; Asunción Molina; Rosa María Blanco; Manuel Sánchez-Sánchez (Catalysts, 2020)
Metal-organic framework (MOF) materials possess the widest versatility in structure, composition, and synthesis procedures amongst the known families of materials. On the other hand, the extraordinary affinity between MOFs and enzymes has led to widely investigating these materials as platforms to support these catalytic proteins in recent years. In this work, the MOF material NH2-MIL-53(Al) has been tested as a support to immobilize by one-step methodology (in situ) the enzyme lipase CaLB from Candida antarctica by employing conditions that are compatible with its enzymatic activity (room temperature, aqueous solution, and moderate pH values). Once the nature of the linker deprotonating agent or the synthesis time were optimized, the MOF material resulted in quite efficient entrapping of the lipase CaLB through this in situ approach (>85% of the present enzyme in the synthesis media) while the supported enzyme retained acceptable activity (29% compared to the free enzyme) and had scarce enzyme leaching. The equivalent post-synthetic method led to biocatalysts with lower enzyme loading values. These results make clear that the formation of MOF support in the presence of the enzyme to be immobilized substantially improves the efficiency of the biocatalysts support for retaining the enzyme and limits their leaching.